FUTSAL BALL LEARNING MEDIA WITH SIMPLE AND ENVIRONMENTALLY FRIENDLY TOOLS - Nugraha, Hilmi (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
This study aims to produce educational device products based on simple tools in futsal learning at MI MIFTAHUL HUDA 1. This study applies a research approach with the Classroom Action Research (CAR) method. The participants involved are futsal extracurricular participants at MI MIFTAHUL HUDA 1. For data collection instruments in the form of planning, action, observation and reflection by observing the learning process directly during practice, the results of the overall product trial involving MI MIFTAHUL HUDA 1 students in a group trial with a sample of 33 students. By utilizing these simple tools, futsal learning can be done in a fun, practical, and more accessible way to the wider community. In addition, the use of environmentally friendly tools is also expected to foster awareness of the importance of environmental conservation among students. The results of this study indicate that the use of futsal ball learning media with simple and environmentally friendly tools is not only effective in improving futsal skills, but can also have a positive impact on students' environmental awareness. Based on the research results and discussion data, it can be concluded that learning basic futsal techniques with simple tools designed for elementary school students is categorized as very feasible and can be used without changes.